2016
DOI: 10.1002/dta.2134
|View full text |Cite
|
Sign up to set email alerts
|

Purity and adulterant analysis of some recent drug seizures in Italy

Abstract: The data collected in this study describe an initial attempt to systematically introduce the qualitative and quantitative analysis of adulterants present in seized street drugs in Italy with the aim of improving surveillance and data sharing and for this purpose, the implementation of validated and standardized procedures are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…The purity of heroin, by-products, impurities and concentration, and nature of adulterants varies from sample to sample in street heroin. The most common adulterants are caffeine, acetaminophen (Andreasen et al, 2009;Broséus et al, 2016a;Broséus et al, 2016b), dextromethorphan (Chan et al, 2012), phenobarbital, acetylthebaol, diazepam, clonazepam, pheniramine, biperiden, tramadol (Akhgari et al, 2012, chloroquine (Sulaiman et al, 2017) and lidocaine (Pichini et al, 2017). The qualitative analysis of morphia tablets using GC-MS showed that in addition to heroin tablets, sample A also contained caffeine, dextromethorphan, hydromorphone, and acetylcodiene, while sample B contained caffeine acetylcodiene, papaverine, and noscapine ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The purity of heroin, by-products, impurities and concentration, and nature of adulterants varies from sample to sample in street heroin. The most common adulterants are caffeine, acetaminophen (Andreasen et al, 2009;Broséus et al, 2016a;Broséus et al, 2016b), dextromethorphan (Chan et al, 2012), phenobarbital, acetylthebaol, diazepam, clonazepam, pheniramine, biperiden, tramadol (Akhgari et al, 2012, chloroquine (Sulaiman et al, 2017) and lidocaine (Pichini et al, 2017). The qualitative analysis of morphia tablets using GC-MS showed that in addition to heroin tablets, sample A also contained caffeine, dextromethorphan, hydromorphone, and acetylcodiene, while sample B contained caffeine acetylcodiene, papaverine, and noscapine ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Considering frequency of appearance, cocaine adulterants could be divided into three groups: levamisole, phenacetin, lidocaine, boric acid, caffeine, piracetam and diltiazem are included in the first group, characterized by showing a frequency over 5%; the second group, characterized by a frequency under 5% and above 1%, included substances such as procaine, paracetamol, tetracaine and benzocaine. Levamisole has become the most abundant adulterant in cocaine seizures, specifically from 2010, as previously reported in other European countries, and its presence in street cocaine has been linked to agranulocytosis and pulmonary vasculitis with observed serious health hazards and fatalities …”
Section: Cocaine Adulteration: Types Of Adulterants and Weight‐stratimentioning
confidence: 94%
“…Furthermore, the risks associated with the consumption of drugs and the unpredictability of drug effects are a consequence of the undetermined substances frequently present in their composition; this also represents a challenge to emergency department personnel, with a double task of identifying and treating the effects not only of the primary drug, but also of the additional ones …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, the authors present preliminary findings from the analysis of heroin, cocaine, MDMA and amphetamine samples seized by the Carabinieri police between 2013 and 2016. The authors have demonstrated that it is possible to map the differences in drug purities originating in different regions, which highlighted the challenges encountered during data collection and interpretation and that further collaborations with other national police forces are highly desirable …”
Section: The Need For Chemical Profiling and Fingerprintingmentioning
confidence: 99%